A novel strategy to enhance the multiple interface effect using amorphous carbon packaged hydrogenated TiO2 for stable and effective microwave absorption. Issue 20 (7th May 2019) - Xu, Jianle; Sun, Li; Qi, Xiaosi; Wang, Zhongchi; Fu, Qiang; Pan, Chunxu
Abstract : Roe-like B-TiO2 /C nanocomposites were prepared via a one-step method as perfect microwave absorbers. Abstract : The development of efficient strategies for the micro-structural design of microwave absorbers with a thin layer thickness, broad bandwidth, and strong absorption intensity remains a great challenge. In this study, hydrogenated black TiO2 (B-TiO2 ) nanoparticles (NPs) wrapped by an amorphous carbon (B-TiO2 /C) composite were successfully synthesized via a one-step hydrogenation–carbonization method for the first time. The structures and performances of the B-TiO2 /C composites could be adjusted by simply altering the carbonization time. The complex permittivity performances of B-TiO2 /C under different carbonization times were investigated to optimize its composite structure, which could distinctly enhance its electromagnetic (EM) wave absorption property. The minimum reflection loss (RL) value of −73.2 dB in the "roe"-like B-TiO2 /C was obtained and the effective absorption bandwidth was measured to be 6.8 GHz with a thin thickness of 1.5 mm. The superior microwave absorbing property of the composites originates from the improvement of the impedance matching with the coating of amorphous carbon, which increased the multiple relaxation processes.